Effect of Assisted Reproductive Technology on the Occurrence of Birth Defects: A Population-Based Study [25P]. (May 2017) - Maor, Gil Shechter; Czuzoj-Shulman, Nicholas; Spence, Andrea; Abenhaim, Haim Arie
Abstract : INTRODUCTION: Studies have shown that births conceived with Assisted Reproductive Technology (ART) may be associated with a greater risk of birth defects compared with non-ART births. The purpose of our study is to evaluate the association between ART and births defects using a large population-based database set in the United States. METHODS: We used the Centers for Disease Control and Prevention's Period linked birth-infant death data files and fetal death database for 2011 to 2013 to conduct a retrospective cohort study consisting of live births during that period. Multivariate logistic regression was used to determine the adjusted effect of ART on birth defects, both overall and by specific defects. RESULTS: Between 2011 and 2013 there were 11, 862, 780 live births, of which 11, 791, 730 were spontaneous pregnancies and 71, 050 were conceived by ART, with an increasing trend in incidence of ART during this 3-year period and an overall increasing trend of birth defects during the study period. Overall, infants conceived by ART had a greater risk of having birth defects compared with infants conceived spontaneously (77/10, 000 vs 24/10, 000, respectively, OR 2.20, 95% CI 2.00-2.42). The most malformation most commonly associated with ART was cyanotic heart defects (OR 2.74, 95% CI 2.42-3.09) while other malformations included cleft lip and/or palate and hypospadias. CONCLUSION: There is an increased risk of birth defects, overall and of specific types, in the ART population. Appropriate counseling and specialized ultrasound evaluations should be considered in pregnancies conceived by ART